The Significance of Habitat Characteristics to the Spatial Distribution of Local Avian Assemblage at Gannoruwa Mountain Forest Reserve, Kandy, Sri Lanka. (27th July 2016) - Rathnayake, D. G. R. M. M. Kaushalya; Ileperuma Arachchi, I. Sandunika; Pathirana, Buwaneka S.; Wickramasinghe, S.
Abstract : Distribution patterns corresponding to habitat characteristics in tropical forests have not been largely studied. Natural forest structure as well as the anthropogenic alterations to the forests equally affects the distribution patterns of wet zone avifauna. The study reveals the importance of % canopy closure, distance from the forest edge, tree density, diversity, and elevation to the community composition of local forest birds inhabiting Gannoruwa Forest Reserve, Sri Lanka. The most important factors resulting in the study for shaping the avian distribution pattern are distance from the edge, elevation, and the % canopy closure. With the increase of favouring resources to the avian fauna at the edges and the juxtaposition of the edge, many forest loving species were observed to move towards the edge. The pattern is proven advantageous, but harmful in the long run. Thus, it is advisable that the conservation plans should focus on habitat destruction and the anthropogenic disturbance along forest edges.